2013
DOI: 10.1088/0004-637x/771/2/110
|View full text |Cite
|
Sign up to set email alerts
|

B- And a-Type Stars in the Taurus-Auriga Star-Forming Region

Abstract: We describe the results of a search for early-type stars associated with the Taurus-Auriga molecular cloud complex, a diffuse nearby star-forming region noted as lacking young stars of intermediate and high mass. We investigate several sets of possible O, B, and early A spectral class members. The first is a group of stars for which mid-infrared images show bright nebulae, all of which can be associated with stars of spectral-type B. The second group consists of early-type stars compiled from (1) literature li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 75 publications
1
23
1
Order By: Relevance
“…To investigate its origin, we have inspected the SPIRE images of B7/L1495 at different wavelengths. These images show that B7/L1495-south lies inside a region of bright and extended farinfrared emission in the vicinity of V892 Tau, a Herbig Ae/Be star first identified by Elias (1978) and with a total luminosity of ≈400 L (Sandell et al 2011;Mooley et al 2013) that lies about 300 (0.2 pc) in projection from B7/L1495-south. A grey body analysis of the SPIRE emission, indicates that the dust temperature in the region is elevated, and that it gradually increases toward V892 Tau, where it reaches about 15 K, or 50% higher than in B7/L1495-north.…”
Section: Comparison With Spire Data and N 2 H + Abundancementioning
confidence: 77%
“…To investigate its origin, we have inspected the SPIRE images of B7/L1495 at different wavelengths. These images show that B7/L1495-south lies inside a region of bright and extended farinfrared emission in the vicinity of V892 Tau, a Herbig Ae/Be star first identified by Elias (1978) and with a total luminosity of ≈400 L (Sandell et al 2011;Mooley et al 2013) that lies about 300 (0.2 pc) in projection from B7/L1495-south. A grey body analysis of the SPIRE emission, indicates that the dust temperature in the region is elevated, and that it gradually increases toward V892 Tau, where it reaches about 15 K, or 50% higher than in B7/L1495-north.…”
Section: Comparison With Spire Data and N 2 H + Abundancementioning
confidence: 77%
“…One of them, HD 27778 (62 Tau), is in the direction of the Taurus star-forming region at a projected separation of ∼1°.5 from DF Tau and ∼1°.9 from DG Tau and FZ Tau. At a distance of 225 pc, as measured by Hipparcos (ESA 1997), HD 27778 is not a Taurus member but likely belongs to the older Cas-Tau OB association located behind the Taurus molecular cloud (e.g., Mooley et al 2013). The K I profile obtained by Welty & Hobbs (2001) shows two deep and spectrally resolved absorptions at ∼14.8 km s −1 (consistent with the DF Tau and DG Tau Na I and K I velocities) and ∼18.5 km s −1 (slightly lower than the FZ Tau velocities).…”
Section: Origin Of the Narrow Absorption In The Na I And K I Profilesmentioning
confidence: 91%
“…It would be premature to conclude that the true Taurus IMF is different until a comprehensive study of F-K stars has been conducted. Furthermore, Mooley et al (2013) have identified a number of B-A stars in Taurus that might significantly modify the inferred IMF, although their membership has been disputed (e.g., Esplin et al 2014), and Herczeg & Hillenbrand (2014) have found that some Taurus members were significantly misclassified when originally observed in the 1960s and 1970s. We therefore suggest that the shape of the Taurus IMF is not yet settled.…”
Section: Implications For the Initial Mass Functionmentioning
confidence: 99%